Preparation method and application of lithium inner salt zwitterionic polymer electrolyte
By free -radical polymerization prepares bisexual ion polymer containing lithium salt, and forms electrolyte electrolytes in lithium -in -sexual ion polymer, solving the safety problem of organic electrolyte in the lithium -ion battery, and improving the performance and safety of the battery.
Patent Information
- Application Number
- CN202310916549.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-25
- Publication Date
- 2025-01-28
AI Technical Summary
The organic electrolyte used in existing lithium-ion batteries has high volatility and flammability, resulting in frequent fire and explosion accidents, and the room temperature ion conductivity of polymer electrolytes is low, the electrochemical window is narrow, and it is unstable to lithium metal. Limits its practical application.
By combining dual -based dual -based dual -based cylinder ionic liquids and dual -key sulfonate salt salts, the dual -containing cyclical ionic salt contains lithium -containing salt polymer, and a thin film material is formed by heating melting thermal pressure. Electrolytes of salt two -sex ion polymer.
Improve the safety, thermal stability, lithium ion migration and electrochemical windows of lithium -ion batteries, and at the same time enhanced ion conductivity, suitable for electrochemical energy storage devices such as lithium -ion batteries, supercapacitors, lithium sulfur batteries or solar batteries Essence
Smart Images

Figure CN119371592A_ABST
Abstract
Description
Technical field:
[0001] The invention relates to the technical field of polymer electrolytes, and in particular to a preparation method of a lithium inner salt zwitterionic polymer electrolyte and application thereof. Background technology:
[0002] In recent years, with the application of lithium-ion batteries, fire and explosion accidents caused by lithium-ion batteries are common. The organic electrolytes used in large quantities in lithium-ion batteries are highly volatile and flammable, which is the main cause of battery safety problems. Compared with the use of organic electrolytes, the use of polymer electrolytes (PEs) that are leak-proof and have good compatibility with lithium metal can effectively solve the above problems. At present, researchers have developed a variety of polymer electrolyte matrices including polyethylene oxide (PEO), polyacrylonitrile (PAN), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) and polymethyl methacrylate (PMMA). Although these polymer matrices show good properties in some polymer electrolytes, their practical applications are limited by low room temperature ionic conductivity, narrow electrochemical window, instability to lithium metal and poor mechanical strength. Although people continue to improve the electrochemical properties of existing polymer electrolyte matrices through blending, compounding, cross-linking and other methods, it is imperative to develop new polymer electrolyte matrices. Ionic polymer materials (PILs) derived from ionic liquids have attracted the interest of many scientific researchers.
[0003] Most ionic polymer materials (PILs) are polycationic systems, with free anions and the need for additional lithium salts to provide lithium ions. Free anions easily form concentration polarization at the negative electrode, affecting the transmission of lithium ions and causing battery performance to decline. To solve this problem, zwitterionic polyion salts with multiple functional groups have attracted people's interest. Summary of the invention:
[0004] The purpose of the present invention is to provide a lithium inner salt zwitter ion polymer and a preparation method and application of a lithium inner salt zwitter ion polymer electrolyte.
[0005] The present invention is achieved through the following technical solutions:
[0006] A preparation method of a lithium inner salt zwitterionic polymer comprises the following steps: combining a double-bond-containing quaternary ammonium ionic liquid and a double-bond-containing lithium sulfonate salt together through free radical polymerization to form a zwitterionic polymer containing a lithium inner salt; the cation in the double-bond-containing quaternary ammonium ionic liquid is acryloyloxyethyltrimethylammonium (AETA), and the anion is one or more of bistrifluoromethanesulfonyl imide (TFSI-) or bisfluorosulfonyl imide (FSI-); and the double-bond-containing lithium sulfonate salt is 2-acrylamido-2-methylpropanesulfonate lithium (AMPSLi).
[0007] The preparation method of a lithium inner salt zwitterionic polymer specifically comprises the following steps: adding azobisisobutyronitrile (AIBN) into 2-acrylamide-2-methylpropanesulfonic acid lithium (AMPSLi), dissolving a double-bond-containing quaternary ammonium ionic liquid in NMP to prepare a solution, and then dripping it under an argon atmosphere; after the dripping is completed, heating to 60-90°C and reflux reaction until the reaction is completed, a white emulsion state is present in the reaction bottle, and a white solid is obtained after centrifugation, the white solid is washed with ether for multiple times, and then most of the residual solvent is removed in a 40-70°C forced air oven, grinding it into a white powder, and then transferring it to a 110-130°C vacuum oven until the solvent is completely removed to obtain a purified lithium inner salt zwitterionic polymer.
[0008] Preferably, the molar ratio of 2-acrylamide-2-methylpropanesulfonate lithium (AMPSLi) to the double-bond-containing quaternary ammonium ionic liquid is 1:0.5 to 1:2.
[0009] Preferably, the reflux reaction time is 8 to 24 hours.
[0010] The preparation method of the double-bond-containing quaternary ammonium ionic liquid is as follows: acryloxyethyltrimethylammonium chloride (AETACl), a lithium salt and water are stirred at room temperature, then an appropriate amount of dichloromethane is added, a lower organic phase is separated, washed with water, and the liquid is separated, and finally the organic phase is dried with anhydrous magnesium sulfate, and the filtrate is rotary evaporated at room temperature after filtering to obtain a colorless viscous liquid, which is a double-bond-containing quaternary ammonium ionic liquid after anion exchange; the lithium salt is one or more of lithium bistrifluoromethanesulfonyl imide (LiTFSI) and lithium bisfluorosulfonyl imide (LiFSI).
[0011] 2-Acrylamide-2-methylpropanesulfonic acid lithium (AMPSLi) is obtained by acid-base neutralization reaction of 2-acrylamide-2-methylpropanesulfonic acid (AMPS) and lithium hydroxide (LiOH), which specifically comprises the following steps: 2-acrylamide-2-methylpropanesulfonic acid (AMPS) and N-methylpyrrolidone (NMP) are mixed to obtain 2-acrylamide-2-methylpropanesulfonic acid (AMPS) solution, and then LiOH·H 2 O, gradually add it into the AMPS solution in an ice-water bath, and continue stirring until the reaction is complete to obtain a solution of 2-acrylamide-2-methylpropanesulfonic acid lithium (AMPSLi).
[0012] Preferably, the mass fraction of the 2-acrylamide-2-methylpropanesulfonic acid (AMPS) solution is 10-40%.
[0013] The present invention also protects a lithium inner salt zwitter ion polymer electrolyte, which is a film material formed by heating, melting and hot pressing the lithium inner salt zwitter ion polymer and a plasticizer at 120-150°C.
[0014] Preferably, the plasticizer is one or more of ethylene carbonate (EC) and propylene carbonate (PC).
[0015] Preferably, the plasticizer accounts for 50% to 65% of the total mass of the lithium inner salt zwitterionic polymer electrolyte.
[0016] Preferably, the raw material of the lithium inner salt zwitterionic polymer electrolyte further comprises a lithium salt.
[0017] Preferably, the lithium salt is one or more of lithium bistrifluoromethanesulfonyl imide (LiTFSI) and lithium bisfluorosulfonyl imide (LiFSI).
[0018] Preferably, the lithium salt accounts for 0-15% of the total mass of the lithium inner salt zwitterionic polymer electrolyte.
[0019] When the raw material of the lithium inner salt zwitter ion polymer electrolyte further comprises a lithium salt, the preparation method of the lithium inner salt zwitter ion polymer electrolyte comprises the following steps:
[0020] Weigh a lithium inner salt zwitterionic polymer, a plasticizer and a lithium salt, heat the mixture at 120-150° C. to make it liquid, stir it evenly, drop it on a stainless steel sheet, clamp it with another stainless steel sheet while it is hot, and after cooling, a lithium inner salt zwitterionic polymer electrolyte can be obtained.
[0021] Depending on the electrodes of the assembled battery, the stainless steel sheets can be replaced with electrode sheets made of lithium metal, lithium iron phosphate, lithium cobalt oxide, graphite, etc.
[0022] The present invention also protects the application of the lithium inner salt zwitterionic polymer electrolyte to an electrochemical energy storage device, wherein the electrochemical energy storage device is a lithium ion battery, a supercapacitor, a lithium sulfur battery or a solar cell.
[0023] The present invention also provides a composite lithium inner salt zwitterionic polymer electrolyte, which is formed into a dry film by electrostatic spinning or solution casting of a lithium inner salt zwitterionic polymer, other polymer matrices, and a crosslinking agent; the prepared dry film is immersed in a plasticizer or a mixed solution prepared by a plasticizer and a crosslinking agent to form a semi-interpenetrating material in situ gelation, namely the composite lithium inner salt zwitterionic polymer electrolyte; wherein the mass ratio of the lithium inner salt zwitterionic polymer to the other polymer matrices is 9:1-6:4; in the mixed solution prepared by the plasticizer and the crosslinking agent, the mass content of the plasticizer is not less than 75wt%, and the remainder is the crosslinking agent. Other polymer matrices are one or more water-soluble polymers such as polyethylene oxide (PEO, average molecular weight of 100,000 to 1,000,000), polyvinyl alcohol (PVA, average molecular weight of 100,000 to 200,000), and polyacrylamide (PAM, average molecular weight of 4 to 18,000,000); the plasticizer is an electrolyte for lithium-ion batteries, in which the solute is one or more of lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethyl)sulfonyl imide (LiTFSI), and lithium bis(fluorosulfonyl) imide (LiFSI); the solvent is ethylene carbonate (EC), carbon The crosslinking agent is one or more of adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, ethylenediaminetetraacetic acid, polyethylene glycol dicarboxylic acid (HOOC-PEG-COOH, with an average molecular weight of 600 to 2000), tripropylene glycol diacrylate (TPGDA), ethylene glycol dimethacrylate (EGDMA), and trimethylolpropane triacrylate (TMPTA).
[0024] The present invention also protects the application of the composite lithium inner salt zwitterionic polymer electrolyte in electrochemical energy storage devices, wherein the electrochemical energy storage device is a lithium ion battery, a supercapacitor, a lithium sulfur battery or a sodium ion battery.
[0025] The beneficial effects of the present invention are as follows: the present invention combines quaternary ammonium ions of quaternary ammonium type ionic liquids containing double bonds with sulfonate groups in double-bond lithium sulfonate salts through free radical copolymerization to synthesize a zwitterionic polymer containing lithium inner salt, and thereby obtains two polymer electrolytes. Compared with the currently widely used traditional organic liquid electrolytes, the polymer electrolytes have higher safety, thermal stability, lithium ion migration number and electrochemical window, and also have higher ionic conductivity, and can be widely used in electrochemical energy storage devices such as lithium ion batteries, supercapacitors, lithium sulfur batteries or solar cells. Description of the drawings:
[0026] Figure 1 Schematic diagram of the reaction of the lithium inner salt zwitterionic polymer (P(AMPSLi-IL)) in Example 1.
[0027] Figure 2 It is the hydrogen nuclear magnetic resonance spectrum of acryloyloxyethyltrimethylammonium chloride (AETACl), 2-acrylamide-2-methylpropanesulfonic acid (AMPS) and lithium inner salt zwitterionic polymer (P(AMPSLi-IL)) in Example 1.
[0028] Figure 3 The Raman spectra (700-800 cm) of the lithium inner salt zwitterionic polymer (P(AMPSLi-IL)) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) in Example 1 are shown in Table 1. -1 ).
[0029] Figure 4 1 is the differential scanning calorimetry (DSC) curve of the lithium inner salt zwitterionic polymer (P(AMPSLi-IL)) in Example 1.
[0030] Figure 5 It is the thermogravimetric curve (TG) of the lithium inner salt zwitterionic polymer (P(AMPSLi-IL)) in Example 1 and the fiber membrane in Example 5.
[0031] Figure 6 is a photograph of the lithium inner salt zwitterionic polymer electrolyte (P(AMPSLi-IL)-EC) in Example 2.
[0032] Figure 7 The lithium inner salt zwitterionic polymer electrolyte (P(AMPSLi-IL)-EC) and organic liquid electrolyte (LE, 1 mol / L LiTFSIinDME:DOL=1:1, v:v+1%LiNO in Example 2) are used. 3 )’s LSV curve.
[0033] Figure 8 It is a flow chart for preparing the composite lithium inner salt zwitterionic polymer electrolyte in Examples 5, 6, 7 and 8.
[0034] Fig. 9 is the differential scanning calorimetry (DSC) curve of the fiber membrane in Example 5.
[0035] Fig.10 This is a comparison of the thermal dimensional stability of the fiber membrane in Example 5 and the commercial diaphragm.
[0036] Fig.11 It is the stress-strain curve of the fiber membrane in Examples 5, 6, 7 and 8.
[0037] Fig.12 This is the fiber membrane folding and unfolding test in Example 5.
[0038] Fig.13 These are photographs of the fiber membranes in Examples 5, 6, 7, and 8 taken under a scanning electron microscope (SEM).
[0039] Fig.14 It is the fitting straight line of the composite lithium inner salt zwitterionic polymer electrolyte lgσ~1000 / T in Example 5.
[0040] Fig.15 It is the LSV curve of the composite lithium inner salt zwitterionic polymer electrolyte and the organic liquid electrolyte (1 mol / LLiFSI inEC) in Example 5.
[0041] Fig.16 The chronoamperometric (CA) curves of the composite lithium inner salt zwitterionic polymer electrolyte and the organic liquid electrolyte (1 mol / L LiFSI inEC) at room temperature in Example 5, and the electrochemical impedance spectroscopy (EIS) spectra before and after polarization.
[0042] Fig.17 The lithium plating / stripping tests at different current densities were performed on a lithium-lithium symmetric battery assembled using the composite lithium inner salt zwitterionic polymer electrolyte and an organic liquid electrolyte (1 mol / L LiFSIinEC) in Example 5.
[0043] Fig.18 The test was carried out on a lithium iron phosphate half-cell assembled with the composite lithium inner salt zwitterionic polymer electrolyte in Example 5 at a current density of 0.5C. Specific implementation method:
[0044] The following is a further description of the present invention, rather than a limitation of the present invention.
[0045] Embodiment 1:
[0046] The specific preparation steps of lithium inner salt zwitterionic polymer are as follows:
[0047] (1) Add 31.19 g (0.129 mol) of 80 wt% aqueous solution of acryloyloxyethyl trimethylammonium chloride (AETACl) and 40 g (0.139 mol) of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) to a 150 ml conical flask, add 20 ml of water, and stir at room temperature for 6 h. Then add 30 ml of dichloromethane, separate the lower organic phase, wash with 50 ml of water, let stand and separate the liquids, and repeat the washing five times. Finally, add 3.00 g of anhydrous magnesium sulfate to the organic phase and let stand for 2 h. After filtering, evaporate the filtrate at room temperature to obtain a colorless viscous liquid, which is the ionic liquid AETATFSI, with a yield of 56.48 g and a yield of 94.98%.
[0048] (2) In a 150 ml round-bottom three-necked flask in an ice-water bath, weigh 3.88 g (18.35 mmol) of 2-acrylamide-2-methylpropanesulfonic acid (AMPS), add NMP to prepare a 30% solution. Also weigh LiOH·H 2 O0.77g (18.35mmol) was added into the AMPS solution in an ice-water bath three times. After the addition was completed, the reaction was continued with stirring for 2h to obtain 2-acrylamide-2-methylpropanesulfonic acid lithium (AMPSLi, 18.35mmol) solution.
[0049] (3) Add 0.18 g (1.10 mmol) of recrystallized azobisisobutyronitrile (AIBN) to the three-necked flask where the reaction in step (2) is completed, and then install a thermometer, condenser and dropping funnel. Weigh 8.04 g (18.35 mmol) of AETATFSI, dissolve it in NMP to prepare a 30 wt% solution, and transfer it to the dropping funnel. Under stirring, introduce argon gas into the reaction system for 1 hour to remove the air in the system, and then drip the AETATFSI solution into the reaction bottle drop by drop. The dripping is completed in about 1 hour. After the dripping is completed, the temperature is raised to 75°C and maintained for 12 hours.
[0050] (4) After the reaction in step (3) is completed, a white emulsion appears in the reaction bottle. After centrifugation, a white solid is obtained. The solid is washed with ether, and the process is repeated three times. The solid is then kept in a forced air oven at 60°C for 6 hours to obtain a hard, brittle and highly absorbent white solid. The solid is ground into a white powder in a mortar and then transferred to a vacuum oven at 120°C for 12 hours to obtain 7.04 g of purified lithium inner salt zwitterionic polymer (P(AMPSLi-IL)) with a yield of 59%.
[0051] The reaction diagram of the lithium inner salt zwitterionic polymer (P(AMPSLi-IL)) described in Example 1 is as follows: Figure 1 shown.
[0052] Acryloyloxyethyltrimethylammonium chloride (AETACl), 2-acrylamide-2-methylpropanesulfonic acid (AMPS) and the obtained lithium inner salt zwitterionic polymer (P(AMPSLi-IL)) were detected by nuclear magnetic resonance hydrogen spectrum, and the deuterated reagent was heavy water. The measured nuclear magnetic resonance hydrogen spectrum is as follows Figure 2As shown. In the P(AMPSLi-IL) NMR hydrogen spectrum, the double bond peak disappears, and a broad peak appears at δ=2.57-1.45, indicating that the product has been completely polymerized. The peak area at B is set to 2, representing the two hydrogens on the methylene connected to N. The other peaks are integrated, and the peak area at A is 10.85, which means that the hydrogen peaks from the three methyl groups in AETATFSI and the hydrogen peaks from the methylene in AMPS overlap. The peak areas at other positions can also correspond to the product structure. It can be proved that AETATFSI and AMPSLi are polymerized in a molar ratio of 1:1.
[0053] Raman spectra of lithium inner salt zwitterionic polymer (P(AMPSLi-IL)) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) are shown in Figure 2. Figure 3 As shown, the light source is 633nm laser, the tested power is 0.1mW, the integration time is 10s, the objective lens magnification is 20x, and the interception is 700-800cm -1 In the Raman spectrum of LiTFSI, 749.6cm -1 The peak at 751.2 cm indicates SNS bending vibration. -1 The place should be TFSI in LiTFSI - SNS bending vibration, 741.4cm -1 The peak at represents TFSI bound to the quaternary ammonium cation - , indicating the existence of crystalline LiTFSI inner salt in P(AMPSLi-IL).
[0054] The differential scanning calorimetry (DSC) curve of lithium inner salt zwitterionic polymer (P(AMPSLi-IL)) is as follows: Figure 4 As shown in the figure, the temperature range is 30-250℃, and the heating rate is 10℃ / min. A melting point of 197℃ appears in the first heating scan of P(AMPSLi-IL), indicating that it contains crystalline LiTFSI. The melting point peak disappears in the second heating scan, indicating that P(AMPSLi-IL) is converted into an amorphous structure after heating, and its glass transition temperature is 221℃.
[0055] Thermogravimetric curve (TG) of lithium inner salt zwitterionic polymer (P(AMPSLi-IL)) is as follows Figure 5 As shown, the temperature range is 30-800℃, and the scanning speed is 10℃ / min. The significant thermal decomposition temperature of P(AMPSLi-IL) is 295℃, and the main mass loss range is 300-500℃.
[0056] Embodiment 2:
[0057] The specific preparation steps of lithium inner salt zwitterionic polymer electrolyte are as follows:
[0058] In a glove box filled with argon, weigh 0.2g of lithium inner salt zwitterionic polymer (P(AMPSLi-IL)) and 0.35g of ethylene carbonate (EC) and add them into a glass bottle. Heat at 150°C on a heating stirrer until the solid melts, stir evenly and drip onto a stainless steel sheet, clamp with another stainless steel sheet while hot, and cool to obtain a lithium inner salt zwitterionic polymer electrolyte (P(AMPSLi-IL)-EC) ( Figure 6 ).
[0059] The ionic conductivity of the lithium inner salt zwitterionic polymer electrolyte (P(AMPSLi-IL)-EC) is 2.30×10 -4 S cm -1 (25℃), the oxidation potential can reach 5.27V( Figure 7 ), compared with the traditional organic liquid electrolyte (1mol / LLiTFSIinDME:DOL=1:1,v:v+1%LiNO 3 ) has an oxidation potential of 4.59 V, and the P(AMPSLi-IL)-EC polymer electrolyte has better electrochemical stability.
[0060] Embodiment 3:
[0061] The specific operation process is the same as that of Example 2, except that:
[0062] 0.03 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) was weighed and added to the mixed system to obtain a lithium inner salt zwitterionic polymer electrolyte (P(AMPSLi-IL)-EC-LiTFSI).
[0063] The ionic conductivity of the lithium inner salt zwitterionic polymer electrolyte (P(AMPSLi-IL)-EC-LiTFSI) is improved to 8.36×10 -4 S cm -1 (25℃).
[0064] Embodiment 4:
[0065] The specific operation process is the same as that of Example 2, except that:
[0066] 0.03 g of lithium bis(fluorosulfonyl)imide (LiFSI) was weighed and added to the mixed system to obtain a lithium inner salt zwitterionic polymer electrolyte (P(AMPSLi-IL)-EC-LiFSI).
[0067] The ionic conductivity of the lithium inner salt zwitterionic polymer electrolyte (P(AMPSLi-IL)-EC-LiFSI) is improved to 1.07×10 compared with that of P(AMPSLi-IL)-EC. -3 S cm -1 (25℃).
[0068] Embodiment 5:
[0069] The specific preparation steps of the composite lithium inner salt zwitterionic polymer electrolyte are as follows:
[0070] (1) First, a 10 wt% polyvinyl alcohol (PVA) aqueous solution was prepared. 10 g of PVA was weighed into a glass bottle, 90 ml of water was added, and the mixture was stirred in an oil bath at 60° C. for 12 h to obtain a transparent uniform solution.
[0071] (2) 5 g of PVA solution (containing 0.5 g of PVA) was measured, and then lithium inner salt zwitterionic polymer (P(AMPSLi-IL)) was added thereto at a mass ratio of PVA:P(AMPSLi-IL) of 9:1, and then 0.02 g of polyethylene glycol dicarboxylic acid (HOOC-PEG-COOH, Mn=600 g / mol) was added as a cross-linking agent. The solution was stirred at room temperature for 6 h, and then ultrasonicated for 0.5 h to eliminate bubbles, thereby obtaining a uniform and transparent spinning solution.
[0072] (3) The spinning solution was sucked into a 10 ml syringe and then connected to a spinning machine. Aluminum foil was wrapped around the receiving part of the spinning machine drum so that the rough surface of the aluminum foil was outside to receive the nanofibers. The spinning machine condition parameters were set as follows: injection speed was 0.6 ml / h, working voltage was 25 kV, receiving distance was 20 cm, receiving drum speed was 50 rpm, the stainless steel needle for spraying the solution was 22# (orange), a dehumidifier was used to maintain the indoor humidity at ~30% RH, and the room temperature was maintained at 25°C.
[0073] (4) After step (3), turn off the injection pump and the working voltage, remove the nanofiber membrane from the aluminum foil, sandwich it between two flat glass plates, place it in a vacuum oven at 120°C for 12 hours to form a cross-linked structure, and then roll it flat on a roller press. Cut the fiber membrane into discs with a diameter of 16 mm using a slicer, place it in a vacuum oven at 120°C for 12 hours, and then transfer it to a glove box filled with argon.
[0074] (5) Prepare 1 molL -1 The EC solution of LiFSI is used as the electrolyte absorbed by the gel electrolyte. A crosslinking agent tripropylene glycol diacrylate (TPGDA) with a mass fraction of 10% is added to the self-prepared electrolyte. The fiber membrane obtained in step (4) is immersed in the mixed solution and in situ crosslinked under light to obtain a composite lithium inner salt zwitterionic polymer electrolyte (PVA 9-P(AMPSLi-IL) 1 ).
[0075] The composite lithium inner salt zwitterionic polymer electrolyte (PVA) described in Example 5 9 -P(AMPSLi-IL) 1 )) is shown in the preparation flow chart Figure 8 shown.
[0076] The differential scanning calorimetry (DSC) curve of the fiber membrane obtained in step (3) is as follows: Fig. 9 As shown, the temperature range is 30-800℃, and the heating rate is 10℃ / min. In the first heating scan, an endothermic peak centered at 128℃ appeared, corresponding to the heating crosslinking of PVA and HOOC-PEG-COOH. In the second heating scan, its glass transition temperature was observed to be 60℃.
[0077] The thermogravimetric curve (TG) of the fiber membrane obtained in step (4) is as follows: Figure 5 As shown, its thermal decomposition curve is similar to that of P(AMPSLi-IL), with a thermal decomposition temperature of 295 °C and a slight increase in the residual carbon content.
[0078] The fiber membrane obtained in step (4) and the commercial separator (Celgard2325) were heated at different temperatures for 1 h to observe their thermal dimensional stability ( Fig.10 ). The commercial diaphragm starts to shrink at 140℃, and shrinks significantly when the temperature rises to 160℃. However, the fiber membrane remains almost unchanged in size from 100℃ to 160℃, showing its good thermal dimensional stability.
[0079] The stress-strain curve of the fiber membrane obtained in step (4) is as follows: Fig.11 As shown, its maximum tensile strength is 13.8MPa and its elongation at break is 167%, which shows excellent mechanical properties. Fig.12 It shows that the fiber membrane can be bent and folded at will. After unfolding, there is no obvious damage or cracks on the surface, indicating that it has excellent flexibility.
[0080] The photo of the fiber membrane obtained in step (4) under a scanning electron microscope (SEM) is as follows: Fig.13 , it can be seen that the fibers are relatively uniform, with a diameter of 200 to 300 nm.
[0081] The lithium inner salt zwitterionic polymer electrolyte (PVA) obtained in step (5) 9 -P(AMPSLi-IL) 1 ) has an ionic conductivity of 2.87×10 -3 S cm -1 (25℃); the migration activation energy is 4.53 kJmol-1 ( Fig.14 ), the oxidation potential is 4.34V (vs.Li / Li + ) is higher than the electrolyte's 3.94V (vs. Li / Li + )( Fig.15 ); the lithium ion migration number is 0.85, which is higher than the electrolyte's 0.24 ( Fig.16 ).
[0082] The lithium inner salt zwitterionic polymer electrolyte (PVA) obtained in step (5) 9 -P(AMPSLi-IL) 1 ) assembled lithium-lithium symmetrical cells, even at 5 mA cm -2 At a high current density, the oscillation voltage is only 18.9mV, and the stable cycle exceeds 1800h without obvious voltage change ( Fig.17 ). The lithium-lithium symmetrical battery assembled with conventional diaphragm + electrolyte has a -2 At a high current density of 600h, the voltage suddenly increased. This indicates that the lithium inner salt zwitterionic polymer electrolyte (PVA 9 -P(AMPSLi-IL) 1 ) and the lithium metal electrode has excellent interfacial stability.
[0083] The lithium inner salt zwitterionic polymer electrolyte (PVA) obtained in step (5) 9 -P(AMPSLi-IL) 1 ) assembled lithium iron phosphate half-cell, whose initial discharge capacity at 0.5C current density was 145.7 mAh g -1 , the capacity retention rate after 200 cycles is 79.0%, and the average coulombic efficiency exceeds 99.9% ( Fig.18 ). However, the lithium iron phosphate half-cell assembled with conventional diaphragm + electrolyte cannot be cycled normally because the LiFSI salt can corrode the aluminum foil at low potential.
[0084] Embodiment 6:
[0085] The specific operation process is the same as that of Example 5, except that:
[0086] In step (2), the mass ratio of PVA:P(AMPSLi-IL) is 8:2, and a composite lithium inner salt zwitterionic polymer electrolyte (PVA 8 -P(AMPSLi-IL) 2 ).
[0087] Scanning electron microscope (SEM) photos of fiber membranes Fig.13 , which is not much different from the fiber membrane in Example 5; the stress-strain curve is as follows Fig.11, its tensile strength and elongation at break are both less than those in Example 5. Composite lithium inner salt zwitterionic polymer electrolyte (PVA 8 -P(AMPSLi-IL) 2 ) has an ionic conductivity of 2.56×10 -3 S cm -1 (25℃).
[0088] Embodiment 7:
[0089] The specific operation process is the same as that of Example 5, except that:
[0090] In step (2), the mass ratio of PVA:P(AMPSLi-IL) is 7:3, and a composite lithium inner salt zwitterionic polymer electrolyte (PVA 7 -P(AMPSLi-IL) 3 ).
[0091] Scanning electron microscope (SEM) photos of fiber membranes Fig.13 Compared with the fiber membrane in Example 5, some fibers are adhered together and the fiber diameter becomes thicker; the stress-strain curve is as follows Fig.11 , its tensile strength and elongation at break are both less than those in Example 5. Composite lithium inner salt zwitterionic polymer electrolyte (PVA 7 -P(AMPSLi-IL) 3 ) has an ionic conductivity of 2.12×10 -3 S cm -1 (25℃).
[0092] Embodiment 8:
[0093] The specific operation process is the same as that of Example 5, except that:
[0094] In step (2), the mass ratio of PVA:P(AMPSLi-IL) is 6:4, and a composite lithium inner salt zwitterionic polymer electrolyte (PVA 6 -P(AMPSLi-IL) 4 ).
[0095] Scanning electron microscope (SEM) photos of fiber membranes Fig.13 Compared with the fiber membrane in Example 5, some of its fibers are adhered together, the fiber diameter becomes thicker, and solid particles can be observed; the stress-strain curve is as follows Fig.11 , its tensile strength and elongation at break are both less than those in Example 5. Composite lithium inner salt zwitterionic polymer electrolyte (PVA 6 -P(AMPSLi-IL) 4 ) has an ionic conductivity of 1.83×10 -3 S cm-1 (25℃).
[0096] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, simplifications, etc. made without departing from the spirit and principle of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a lithium inner salt zwitterionic polymer, characterized in that: The method comprises the following steps: combining a quaternary ammonium ionic liquid containing a double bond and a lithium sulfonate salt containing a double bond together through free radical polymerization to form a zwitterionic polymer containing a lithium inner salt; the cation in the quaternary ammonium ionic liquid containing a double bond is acryloyloxyethyl trimethylammonium, and the anion is one or more of bistrifluoromethanesulfonyl imide or bisfluorosulfonyl imide; and the lithium sulfonate salt containing a double bond is 2-acrylamide-2-methylpropane sulfonate lithium.
2. The method for preparing a lithium inner salt zwitterionic polymer according to claim 1, characterized in that: The specific steps include: Azobisisobutyronitrile is added to lithium 2-acrylamide-2-methylpropanesulfonate, a quaternary ammonium ionic liquid containing a double bond is dissolved in NMP to prepare a solution, and then the solution is added dropwise under an argon atmosphere. After the dropwise addition is completed, the temperature is raised to 60-90° C. and the solution is refluxed to react until the reaction is completed. A white emulsion state is present in the reaction bottle. After centrifugation, a white solid is obtained. The white solid is washed with ether for multiple times, and then most of the residual solvent is removed in a 40-70° C. forced air oven, ground into a white powder, and then transferred to a 110-130° C. vacuum oven until the solvent is completely removed to obtain a purified lithium inner salt zwitterionic polymer. The molar ratio of lithium 2-acrylamide-2-methylpropanesulfonate to the quaternary ammonium ionic liquid containing a double bond is 1:0.5-1:
2.
3. The method for preparing a lithium inner salt zwitterionic polymer according to claim 2, characterized in that: The reflux reaction time is 8 to 24 hours.
4. The method for preparing a lithium inner salt zwitterionic polymer according to claim 2, characterized in that: The lithium acrylamide-2-methylpropane sulfonate is obtained by acid-base neutralization reaction of 2-acrylamide-2-methylpropane sulfonic acid and lithium hydroxide, and specifically comprises the following steps: 2-acrylamide-2-methylpropane sulfonic acid and N-methylpyrrolidone are mixed to obtain a 2-acrylamide-2-methylpropane sulfonic acid solution, and then LiOH·H2O is gradually added to an AMPS solution in an ice water bath, and after the addition is completed, stirring is continued until the reaction is complete to obtain a solution of lithium 2-acrylamide-2-methylpropane sulfonate.
5. A lithium inner salt zwitterionic polymer electrolyte, characterized in that: A film material formed by heating, melting and hot pressing the lithium inner salt zwitterionic polymer and plasticizer at 120-150°C; the plasticizer is one or more of ethylene carbonate and propylene carbonate; the plasticizer accounts for 50% to 65% of the total mass of the lithium inner salt zwitterionic polymer electrolyte.
6. The lithium inner salt zwitterionic polymer electrolyte according to claim 5, characterized in that: The raw materials of the lithium inner salt zwitterionic polymer electrolyte further include lithium salt; the lithium salt is one or more of lithium bis(trifluoromethanesulfonyl)imide and lithium bis(fluorosulfonyl)imide.
7. The lithium inner salt zwitterionic polymer electrolyte according to claim 6, characterized in that: When the raw materials of the lithium inner salt zwitterionic polymer electrolyte also contain lithium salt, the preparation method of the lithium inner salt zwitterionic polymer electrolyte includes the following steps: weighing the lithium inner salt zwitterionic polymer, plasticizer and lithium salt, heating the mixture to a liquid state at 120 to 150° C., stirring evenly, dripping it on a stainless steel sheet, clamping it with another stainless steel sheet while hot, and obtaining the lithium inner salt zwitterionic polymer electrolyte after cooling; depending on the different electrodes of the assembled battery, the stainless steel sheet can be replaced with lithium metal, lithium iron phosphate, lithium cobalt oxide, or graphite electrode sheets.
8. The use of the lithium inner salt zwitterionic polymer electrolyte according to claim 5, characterized in that: Applicable to electrochemical energy storage devices, wherein the electrochemical energy storage devices are lithium-ion batteries, supercapacitors, lithium-sulfur batteries or solar cells.
9. A composite lithium inner salt zwitterionic polymer electrolyte, characterized in that: A dry film is formed by electrostatic spinning or solution casting of a lithium inner salt zwitterionic polymer, other polymer matrices, and a crosslinking agent; the prepared dry film is immersed in a plasticizer or a mixed solution prepared by a plasticizer and a crosslinking agent to form a semi-interpenetrating material in situ gelation, namely a composite lithium inner salt zwitterionic polymer electrolyte; wherein the mass ratio of the lithium inner salt zwitterionic polymer to the other polymer matrices is 9:1-6:4; in the mixed solution prepared by the plasticizer and the crosslinking agent, the mass content of the plasticizer is not less than 75wt%, and the rest is the crosslinking agent; the other polymer matrix is polyethylene oxide, polyvinyl alcohol and polyacrylamide; the plasticizer is an electrolyte for lithium ion batteries, wherein the solute is one or more of lithium hexafluorophosphate, lithium bis(trifluoromethyl)alkanesulfonyl imide, and lithium bis(fluorosulfonyl)imide, and the solvent is one or more of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, dimethyl carbonate, and diethyl carbonate; the cross-linking agent is one or more of adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, ethylenediaminetetraacetic acid, polyethylene glycol dicarboxylic acid, tripropylene glycol diacrylate, ethylene glycol dimethacrylate, and trimethylolpropane triacrylate.
10. The use of the composite lithium inner salt zwitterionic polymer electrolyte according to claim 9, characterized in that: Applicable to electrochemical energy storage devices, wherein the electrochemical energy storage device is a lithium ion battery, a supercapacitor, a lithium sulfur battery or a sodium ion battery.